ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN ANGGARAN BERBASIS KINERJA (STUDI PADA DINAS PEKERJAAN UMUM KOTA KENDARI) - Wa Ode Apri Yusnita; Manat Rahim (JEP (Jurnal Ekonomi Pembangunan), 2015)
This study aims to determine the factors that affect performance-based budgeting in the Office of Public Works Kendari City. The scope of this study covers human resource competency, leadership style, teamwork, and work system factors. Â The data used in this study consisted of primary data and secondary data. The population in this study were all employee in the Office of Public Works Kendari City with a sampling technique, the number of samples was 30 respondents. The data analysis used is descriptive analysis. The results of the study showed that the factors of human resource competency, leadership style, teamwork, and work system were quite effective against performance-based budgeting.